(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Learning that same information by consulting a map would be moreeffortful and you would likely be deliberately aware of trying to commit theinformation to memory. Despite its comparatively effortless manner, one commonfallacy about implicit learning is that it does not require attention to thesubject matter. Participants in studies of implicit learning are presence to atask; they are just not deliberately trying to obtain certain aspects of thetask stimuli that are the focus of later testing.